Implementation of a grid-tied emergency back-up power supply for medium and low power application - Dhiman Chowdhury; Mohammad Sharif Miah; Md. Feroz Hossain; Uzzal Sarker (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Emergency back-up power supply units are necessary in case of grid power shortage, considerably poor regulation and costly establishment of a power system facility. In this regard, power electronic converters based systems emerge as consistent, = properly controlled and inexpensive electrical energy providers. This paper presents an implemented design of a grid-tied emergency back-up power supply for medium and low power applications. There are a rectifier-link boost derived DC-DC battery charging circuit and a 4-switch push-pull power inverter (DC-AC) circuit, which are controlled by pulse width modulation (PWM) signals. A changeover relay based transfer switch controls the power flow towards the utility loads. During off-grid situations, loads are fed power by the proposed system and during on-grid situations, battery is charged by an AC-link rectifier-fed boost converter. Charging phenomenon of the battery is controlled by a relay switched protection circuit. Laboratory experiments are carried out extensively for different loads. Power quality assessments along with back-up durations are recorded and analyzed. In addition, a cost allocation affirms the economic feasibility of the proposed framework in case of reasonable consumer applications. The test-bed results corroborate the reliability of the research work.